A study on collection development and its organizational pattern of university libraries in Uttar Pradesh (India). Issue 1 (4th January 2016) - Khan, Abdul Mannan
Abstract : Purpose: – The purpose of the study is to know the collection development and its organizational pattern of university libraries in India. Design/methodology/approach: – For the purpose of the study, three sets of questionnaire were prepared by the researcher and furnished to librarians and acquisition librarians (collection development in charge) of these referred libraries. Findings: – The survey reveals that the old centralized universities are better placed in terms of all the parameters of collection development. It is also being revealed that there is a difference between the two old centralized and newly centralized universities especially in Babasaheb Bhimrao Ambedkar University, the de-novo centralized university. It has to do a lot in the sphere of information technology (IT) application and IT-enabled services to the users. Furthermore, there is a conspicuous difference between the two categories that the newly centralized universities are highly lagging behind the old centralized universities in organizational patter of collection development. Originality/value: – There are a number of studies on collection development in the world, but this is the first of its kind within Indian Universities.